Survey of learning motivation of elementary school students starting face-to-face learning after the covid 19 pandemic in Bangli regency - I Ketut Manik Asta Jaya (Universitas Kanjuruhan Malang, 2023)
This study aims to determine the level of learning motivation of elementary school students when starting face-to-face learning. This type of research is quantitative research, using survey methods. This research on students' learning motivation in elementary schools took Bangli Regency. Data collection is done by distributing surveys using Google Forms. The results showed that the dimension of persistence in learning was in the very good category with an average of 82.59%, the dimension of achievement in learning was included in the good category with an average of 76.55%, the independent dimension in learning was included in the very good category with an average percentage of 83.66%. Meanwhile, the dimensions of rewards and punishments in learning are included in the good category with an average percentage of 71.73%. The average percentage of the four dimensions is 78.63%, this result is included in the category of good learning motivation.